Covalent organic framework membrane reactor for boosting catalytic performance - Zheng, Liping; Zhang, Zhengqing; Lai, Zhuozhi; Yin, Shijie; Xian, Weipeng; Meng, Qing-Wei; Dai, Zhifeng; Xiong, Yubing; Meng, Xiangju; Ma, Shengqian; Xiao, Feng-Shou; Sun, Qi (Nature communications, 2024)
Membrane reactors are known for their efficiency and superior operability compared to traditional batch processes, but their limited diversity poses challenges in meeting various reaction requirements. Herein, we leverage the molecular tunability of covalent organic frameworks (COFs) to broaden their applicability in membrane reactors. Our COF membrane demonstrates an exceptional ability to achieve complete conversion in just 0.63 s at room temperature—a benchmark in efficiency for Knoevenagel condensation. This performance significantly surpasses that of the corresponding homogeneous catalyst and COF powder by factors of 176 and 375 in turnover frequency, respectively. The enhanced concentration of reactants and the rapid removal of generated water within the membrane greatly accelerate the reaction, reducing the apparent activation energy. Consequently, this membrane reactor enables reactions that are unattainable using both COF powders and homogeneous catalysts. Considering the versatility, our findings highlight the substantial promise of COF-based membrane reactors in organic transformations. Membrane reactors are efficient alternatives to traditional bath process, yet their limited diversity challenges their applicability to various reaction requirements. Here, the authors report covalent organic framework membrane reactors applied to the Knoevenagel condensation with enhanced performance as compared to homogeneous catalysts.